2021
DOI: 10.1002/aelm.202000939
|View full text |Cite
|
Sign up to set email alerts
|

Regulate the Electron Mobility and Threshold Voltage of P(NDI2OD‐T2)‐Based Organic Field‐Effect Transistors by the Compatibility Principle

Abstract: Blending has been used extensively to meet the requirements for high‐mobility organic field‐effect transistors (OFETs), involving various combinations of (non‐)conjugated polymers and (non‐)conjugated molecules. Nonetheless, the collaborative effects of conjugated polymer and its structurally analogous molecule on charge‐transport properties have rarely been reported. In this work, P(NDI2OD‐T2) and N,N′‐bisbutyl‐2,6‐bis([2,2′]bithiophenyl‐5‐yl)‐1,4,5,8‐naphthalene diimide (M), are synthesized and blended with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The average electron mobility value increased from 1.69 (0 kV cm −1 ) to 2.14 cm 2 V −1 s −1 (0.75 kV cm −1 ), and the 0.75 kV cm −1 sample demonstrated excellent electron mobility performance of up to 3.33 cm 2 V −1 s −1 (Table S2 †). This electron mobility reaches almost the highest level of P(NDI2OD-T2) reported so far [59][60][61][62][63][64][65][66][67][68][69][70][71] (Table S3 †). Furthermore, the electrical performance stability of the 0.75 kV per cm OFET, which showed signicant improvement due to EEF treatment, is nearly similar to, or even better than, that of the 0 kV per cm OFET, which did not undergo EEF treatment (Fig.…”
Section: Electrical Performance Of Ofets Aer Eef Treatmentmentioning
confidence: 80%
“…The average electron mobility value increased from 1.69 (0 kV cm −1 ) to 2.14 cm 2 V −1 s −1 (0.75 kV cm −1 ), and the 0.75 kV cm −1 sample demonstrated excellent electron mobility performance of up to 3.33 cm 2 V −1 s −1 (Table S2 †). This electron mobility reaches almost the highest level of P(NDI2OD-T2) reported so far [59][60][61][62][63][64][65][66][67][68][69][70][71] (Table S3 †). Furthermore, the electrical performance stability of the 0.75 kV per cm OFET, which showed signicant improvement due to EEF treatment, is nearly similar to, or even better than, that of the 0 kV per cm OFET, which did not undergo EEF treatment (Fig.…”
Section: Electrical Performance Of Ofets Aer Eef Treatmentmentioning
confidence: 80%
“…Similar observations can be found in other studies as well. [26][27][28][29] DRS revealed that the E g was not sensitive to the incorporation of the 1,4-butanediylbis(oxy) units in the polymer chain. In principle, the incorporation should interrupt the intramolecular conjugation length, diminishing the intramolecular exciton delocalization length.…”
Section: X-ray Diffraction Of Btb and Btbo Copolymersmentioning
confidence: 99%
“…PDPP4T and PNDI2T were synthesized according to procedures reported in the literature. [32][33][34][35][36] P3HT and PffBT4T were acquired from other sources. Optical and electronic properties of the polymers are summarized in Table 1 and the corresponding spectra are included in the Supporting Information.…”
Section: Preparation and Characterization Of Polymersmentioning
confidence: 99%